Fukuoka triennale 2002 : Imagined workshop. - Fukuoka Asian Art Museum, Fukuoka; Anuar, Zanita; Aye, Thinn Thinn; Chandrasiri, Pradeep; Chenda, So; Choudhury, Subir; Gunaratna, D.M.; Hashmi, Salima; Hideki, Nakamura; Hildawa, Isidro, G.; Kallat, Jitish; Koichi, Yasunaga; et al. (Fukuoka : Fukuoka Asian Art Museum, 2002)
Adipurnomo, Nindityo ; Atelier Bow-Wow ; Chandrasiri, Pradeep ; Chimeddorj, Shagdarjavin ; Chuah Chong Yong ; Harsha, N.S. ; Hitoshi, Ushijima ; Hungchih, Peng ; Hyunsook, Song ; Kaur, Noni ; Khalid, Aisha ; Kunavichayanont, Sutee ; Lee, Nikki S. ; Lin Tian-miao ; Luong, Tran ; Mingtse, Lee ; Omar, Marsidi bin ; Penjor, Tashi ; Perera, Anoli ; Ranjit, Ashmina ; Roy, Alak ; Sabado, John Frank ; Saliankham, Kham Tanh ; Sanpitak, Pinaree ; Shaofeng Chen ; Sharma, Satish ; Sophea, Long ; Suleman, Adeela ; Syed, Risham ; Tun Win Aung ; Vannara, Soeung ; Vijinthanasarn, Panya ; Yau Bee Ling ; Yeondoo, Jung ; Yin Xiuzhen ; Yoshihiro, Suda ; Yukinori, Yanagi
biog. p. 153-160
Engels
Japans
Fukuoka Triennale 2002 : Imagined workshop, FAAM (Fukuoka Asian Art Museum) Fukuoka, 21.03.2002 - 23.03.2002
boek